2013
DOI: 10.1177/197140091302600213
|View full text |Cite
|
Sign up to set email alerts
|

CSF Pressure and Velocity in Obstructions of the Subarachnoid Spaces

Abstract: According to some theories, obstruction of CSF flow produces a pressure drop in the subarachnoid space in accordance with the Bernoulli theorem that explains the development of syringomyelia below the obstruction. However, Bernoulli's principle applies to inviscid stationary flow unlike CSF flow. Therefore, we performed a series of computational experiments to investigate the relationship between pressure drop, flow velocities, and obstructions under physiologic conditions. We created geometric models with dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…Flow abnormalities in the Chiari I patient include flow jets and greater than normal CSF velocities in the foramen magnum and upper cervical spinal canal [1][2][3][4][5] . Flow resistance of the cervical spinal canal 6 and the relative amount of spinal canal obstruction 7 determine the CSF velocities in the spinal canal. The CSF velocities in the upper cervical spinal canal result from longitudinal pressure gradients during portions of the cardiac cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Flow abnormalities in the Chiari I patient include flow jets and greater than normal CSF velocities in the foramen magnum and upper cervical spinal canal [1][2][3][4][5] . Flow resistance of the cervical spinal canal 6 and the relative amount of spinal canal obstruction 7 determine the CSF velocities in the spinal canal. The CSF velocities in the upper cervical spinal canal result from longitudinal pressure gradients during portions of the cardiac cycle.…”
Section: Introductionmentioning
confidence: 99%
“…CSF oscillations are coupled to CSF pressure oscillations that, in the healthy adult, are approximately 90°out of phase with the velocity fluctuations. 2 Elastic properties of the tissues surrounding the subarachnoid space theoretically induce pressure waves, which to date are not fully characterized. 3 With contrast media or radionuclides in the spinal subarachnoid space, a slow convection of fluid is observed resulting from the continuous oscillation of CSF.…”
mentioning
confidence: 99%
“…In the presence of obstruction, the phase difference narrows. 2 Pressure fluctuations in the CSF produce transient pressure waves and gradients in the spinal cord. In portions of the spinal cord with a persistent central canal, pressure on the external surface of the cord may produce radial pressure gradients in the cord.…”
mentioning
confidence: 99%
“…The modeling of CSF flow has been the subject of several computational studies in both patient-specific (Gupta et al 2009;Rutkowska et al 2012;Yiallourou et al 2012;Clarke et al 2013;Helgeland et al 2014) and idealized models (Loth et al 2001;Hentschel et al 2010;Linge et al 2011;Støverud et al 2013;Berselli et al 2014). These studies have demonstrated that the abnormal CSF velocities and pressures are related to abnormal anatomy of the CNS and that computational fluid dynamics capture the flow abnormalities and pressure dissociation observed clinically, although we remark that a comparison between CFD simulations and PC-MR has shown discrepancies (Yiallourou et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…The pressure dissociation is well explained by computational fluid dynamics (CFD), see, e.g. Støverud et al (2013). Prevailing theories therefore suggest that syringomyelia development is mechanically driven by abnormal fluid flow and significant pressure dissociation, and several biomechanical theories have been proposed along this mechanistic reasoning.…”
Section: Introductionmentioning
confidence: 98%